Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic - Zelaya, Diego G.; Güller, Marina (Zootaxa, 2017)
Despite being one of the most speciose families, Epitoniidae still remains at present as one of the least understood gastropod families worldwide. This is a consequence of most of the species being only known from shell morphology, added to the wide intraspecific variability of this character and the fact that shell morphology has proven to have frequent examples of parallelisms and convergences among different (unrelated) species. Knowledge of other morphological and anatomical characters in this group is still in its first steps, and such information is currently available for a limited number of species, thus being difficult (when not impossible) to evaluate its taxonomic value. The aim of this study is to re-evaluate the diversity of Epitoniidae occurring in the Atlantic coast of Patagonia. As part of this study, the validity of only four of the six species described / reported from this area could be confirmed: Epitonium georgettinum, E. striatellum, E. fabrizioi and “Cirsotrema” magellanicum. In addition, three new species were recognized and are described herein: Epitonium evanidstriatum, “Cirsotrema” ctenodentatum and “Cirsotrema” strebeli. Information on the shell (including the protoconch), operculum, radula and jaw for these species is here provided, in most cases for the first time. A neotype for Scalaria magellanica is here designated. Furthermore, “Cirsotrema” georgeanum is here proposed as a replacement name for Scalaria fenestrata Strebel, 1908 (not Meneghini in de Stefani, 1875, nor Scalaria fenestrata Wöhrmann, 1889); and that taxon is regarded as a full species, instead of as a synonym of “Cirsotrema” magellanicum, as suggested in some previous publications. This study reveals that the usage of isolated (either morphological or anatomical) characters is usually insufficient for identifying some of the species from Patagonia; however, if these characters are combined, all species may be clearly recognized.